PENGARUH KUALITAS LAYANAN DAN DIFERENSIASI TERHADAP LOYALITAS NASABAH PADA PT. BANK SULSELBAR CABANG UTAMA MAKASSAR - A. Hadijah Sarjan Irwan Marzuki; Abdul Rahman Kadir; Jumidah Maming (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Service quality and differentiation have an important role in the banking business. This study aims to determine and analyze the effect of service quality on customer loyalty at PT. Bank Sulselbar Main Branch Makassar, as well as to know and analyze the influence of differentiation on customer loyalty at PT. Bank Sulselbar Main Branch of Makassar. The population in this study is all customers who take credit at PT. Bank Sulselbar Main Branch Makassar that is as much as 186 debtors. Sampling technique using accidental sampling technique, the technique of determining the sample by chance at the time the researcher conducted the research and considered eligible it can be used as a sample in this study. Analysis by using computerized system program SPPS release 24. The research findings show that 1) Quality of service has a positive and significant impact on customer loyalty at PT. Bank Sulselbar Main Branch of Makassar. 2) Differentiation have a positive and significant impact on customer loyalty at PT. Bank Sulselbar Main Branch of Makassar. Of the two variables both have a positive effect on customer loyalty.